The Effect of Capital Intensity and Company Size on Tax Aggressiveness with Profitability Moderation - Jennifer Jennifer; Juliandi Sahputra; Latersia Br Gurusinga (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the effect of capital intensity and firm size on tax aggressiveness, with profitability as a moderating variable. The research objects are mining companies listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023, with an observation span of five years. A total of 17 companies were selected as samples using purposive sampling. The data were analyzed using multiple linear regression analysis. The results show that, partially, capital intensity has a positive but insignificant effect on tax aggressiveness, and firm size also has a positive but insignificant effect on tax aggressiveness. Simultaneously, capital intensity and firm size have a positive and significant effect on tax aggressiveness. Based on the moderated regression analysis (MRA), profitability is able to strengthen the influence of capital intensity but is unable to strengthen the influence of firm size on tax aggressiveness.